2010
DOI: 10.1016/j.ijsu.2009.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Simple technique for single incision transumbilical laparoscopic appendectomy

Abstract: Our technique for single incision laparoscopic transumbilical appendectomy is safe feasible, and reproducible. Prospective randomized studies comparing the single incision laparoscopic approach with its conventional multiport counterpart are necessary to confirm the conclusions of our early experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 11 publications
0
37
0
Order By: Relevance
“…Twenty studies [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] including 584 patients met the definition criteria for 'SPILA unassisted' approaches. The use of special multi-conduit ports was reported in four studies [4][5][6][7] ( Fig 1).…”
Section: Spila Unassistedmentioning
confidence: 99%
See 2 more Smart Citations
“…Twenty studies [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] including 584 patients met the definition criteria for 'SPILA unassisted' approaches. The use of special multi-conduit ports was reported in four studies [4][5][6][7] ( Fig 1).…”
Section: Spila Unassistedmentioning
confidence: 99%
“…Techniques placing multiple ports through closely spaced fascial incisions with a single abdominal skin incision were reported in ten studies. [8][9][10][11][12][13][14][15][16][17] Generally, papers described the introduction of three trocars through the fascia, two providing channels for instruments and one providing access for a 5-10mm laparoscopic camera with an angulated lens. In studies where three ports were not placed, a third instrument, often a grasper, was placed directly though a fascial stab incision.…”
Section: Spila Unassistedmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, in the literature one can come across many terms for the same technique [11,12,19]. In the past 10 years there has been substantial progress in the technique, and worldwide apart from cholecystectomy also information on successful appendectomy appeared [20]. Moreover, single reports on splenectomy performed with this technique, large bowel resections, nephrectomy, bariatric procedures or inguinal hernioplasty can be found [19,[21][22][23][24].…”
Section: Resultsmentioning
confidence: 99%
“…4,[12][13][14][15][16][17][18] But the successive rate of SILS technique can be confirmed by prospective clinical trial but no study was found yet.…”
Section: Discussionmentioning
confidence: 98%